(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Stocking density is considered one of the important factors affecting fish growth. The study was aimed to compare the growth parameters of Vietnamese Koi (Anabas testudineus ) at various stocking densities. The experiment was carried out during the period from 01 September to 30 November 2014. Three stocking densities were used as 150, 250 and 350 fries/dec and designated as treatment T1, T2 and T3 respectively each having two replicates. The average size of each pond was 33 decimal with an average depth of 5 feet. Quality fish feed was used three times daily throughout the culture period. From this experiment, it was found that the highest net profit was BDT 32,690 in T1 followed by BDT 36,104 in T2 and BDT 38,450 in T3. That time the market price was BDT 130/kg fish. Culture of Vietnamese koi at stocking density (150 fish/dec) showed higher benefit in short period of time. The benefit cost ratio was 1.7, 1.63 and 1.56 in T1, T2 and T3, respectively. From the present experiment, it was found that the total production was increased with the increase of stocking density. But the individual fish growth rate was decreased with the increase of stocking density. Res. Agric., Livest. Fish.2(2): 335-341, August 2015